LENDING AND LIQUIDITY TO PROFITABILITY - khoer, misbahul; Mutakin, Kikin; Mubaarok, Saeful Huda; Acim; Jaelani, Ihrom (P3M - STAI Kuningan, 2024)
The main problem in this study is profitability in the companies studied with an ROA indicator of 1.3% and is below the good category standard of 1.5%. The purpose of this study is to analyze the extent of the effect together of lending and liquidity on profitability, this study is a descriptive research. The variables in this study are the variables of crediting and liquidity, as independent variables, and profitability, as dependent variables. This research method includes quantitative research in the sense of using numbers, ranging from data collection to interpretation of data with statistical testing. The data analysis technique used in this study is multiple linear regression analysis. From the table it is known that the value of F Calculate is 15.214 it is also known that F table with db2 = n - k - 1 at a confidence level of 5% obtained F table of 4.35. Thus, F calculate > F table = 15.214 > 4.35. This means that there is a positive influence between credit, and liquidity on profitability. To improve lending, PT BPR should promote both customers and the public, for example by offering a faster lending process accompanied by credit interest that can compete with existing banks.